2004
DOI: 10.2346/1.2186772
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Prediction for Cord-Rubber Composite Tires Using a Global-Local Finite Element Method

Abstract: A failure analysis, based on fracture mechanics, may be useful for predicting the lifetime of a cord-reinforced rubber composite pneumatic tire. This paper presents a new three-dimensional Finite Element (FE) local model to calculate the energy release rate at the belt edge region. The new local model uses a three-dimensional (3D) Finite Element Modeling (FEM) fracture analysis based on a steady-state rolling assumption, in conjunction with a global-local technique in ABAQUS. Within the local model, a J-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Subsequently, FCGR data were generated based on equation (2) and plotted on a double logarithmic scale as a function of peak tearing energy. Figure 3 shows the FCGR for both the loading and unloading strokes of the experiment.…”
Section: Fatigue Crack Growth (Fcg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, FCGR data were generated based on equation (2) and plotted on a double logarithmic scale as a function of peak tearing energy. Figure 3 shows the FCGR for both the loading and unloading strokes of the experiment.…”
Section: Fatigue Crack Growth (Fcg)mentioning
confidence: 99%
“…For a known crack of relatively large size, an explicit crack feature can be introduced in a finite element (FE) model to obtain the propagation life based on the crack tip strain energy release rate using the theory of fracture mechanics. [1][2][3][4] Although approximate, Na¨ser et al 5 have shown that tire durability predictions cannot solely be dependent on fracture mechanics parameters but also on other factors, such as strain-induced crystallization (SIC).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of durability, failure most likely initiates when the separation occurs at both steelbelt edge and shoulder zone [14][15][16]. Therefore, a quantitative analysis based on strain energy density is suggested in which both stress and strain can be considered simultaneously in an effort to reflect actual displacement on the interface [17,18]. Hence, the durability of a tire can be relatively evaluated by the strain energy density.…”
Section: Tire Performancementioning
confidence: 99%
“…Finite element method (FEM), extended finite element method (XFEM), and Open Journal of Modelling and Simulation global-local finite element method (GLFEM) are powerful tools for solving the boundary value problems. Tire durability due to large local loading, stiffness discontinuities, and production flaws is frequently related to the fracture of tire components such as belt separation, carcass ply separation, or lug cracking in radial truck tire [1] [2] [3] [4] [5]. Influence factors on fracture and durability of rubber material and tires are manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [8] have studied for the endurance of radial truck tires with finite element modeling by using two approaches: stress analysis parameter approach and tire structure parameter approach. Han et al [3] and Jeong et al [4] performed a failure analysis of truck tires based on fracture mechanics, using a global-local finite element model. The suggested model has proved effective in a variety of analysis for the prediction of tire lifetime.…”
Section: Introductionmentioning
confidence: 99%